Setting the Forestry Carbon Sink Insurance compensation standard for reducing losses from forest fires: An empirical study estimating CO2 emissions from forest fires in a sample of 15 provinces - Lv, Huina; Shi, Anqichen (Frontiers in Environmental Science, 2023)
Forest fires have contributed to increasingly serious global warming by great amount of CO2 emissions and are seen as a loss of carbon sink value, which could be reduced by compensating economically via the Forestry Carbon Sink Insurance. However, estimating loss of carbon stock by estimating carbon emissions of forest fire losses is a crucial step of calculating the loss of carbon sink value. In this research, method proposed by Seiler and Crutzen (1980) was introduced to estimate the carbon emissions as CO2 by in fifteen sample provinces in China by using official data in 2020 ,which would provide a scientific expectation in future. Results show the range of carbon released in the sample provinces and we have estimated for the whole country during 2020——the overall amount of carbon released as CO2 affected by forest fire reached 35017.42–98486.5t, which can be regarded as a loss of 35017.42–98486.5t of forest carbon sequestration capacity. This study supplies one way of estimating loss of carbon sink value and provides evidence from China that the range of carbon stock loss because of forest fires . In practice, this study supports the forestry authorities to participate in the Forestry Carbon Sink Insurance and provides empirical data to establish compensation standards for insurance companies.